α2-Antiplasmin: New Insights and Opportunities for Ischemic Stroke - Reed, Guy L.; Houng, Aiilyan K.; Singh, Satish; Wang, Dong (Seminars in Thrombosis and Hemostasis, 2017)
Thrombotic vascular occlusion is the leading cause of ischemic stroke. High blood levels of α2-antiplasmin (a2AP), an ultrafast, covalent inhibitor of plasmin, have been linked in humans to increased risk of ischemic stroke and failure of tissue plasminogen activator (tPA) therapy. Consistent with these observations, a2AP neutralizes the therapeutic benefit of tPA therapy in experimental stroke. In addition, a2AP has deleterious, dose-related effects on ischemic brain injury in the absence of therapy. Experimental therapeutic inactivation of a2AP markedly reduces microvascular thrombosis, ischemic brain injury, brain swelling, brain hemorrhage, and death after thromboembolic stroke. These data provide new insights into the critical importance of a2AP in the pathogenesis of ischemic brain injury and suggest that transiently inactivating a2AP may have therapeutic value in ischemic stroke.
Keywords: brain infarction; thromboembolism; fibrinolysis; blood–brain barrier; survival